2018
DOI: 10.1101/276394
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The marked diversity of unique cortical enhancers enables neuron-specific tools by Enhancer-Driven Gene Expression

Abstract: SUMMARY 15Understanding neural circuit function requires individually addressing their component parts: specific 16 neuronal cell types. However, the precise genetic mechanisms specifying neuronal cell types remain 17 obscure. While most genes are expressed in the brain, the vast majority are expressed in many different 18 kinds of neurons, suggesting that promoters are not sufficiently specific to distinguish cell types. We 19 therefore examined distal genetic cis-regulatory elements controlling transcription… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…Our prior work showed that identification of cis-regulatory elements uniquely active in finely dissected cortical subregions allows one to generate genetic tools specific to cells in that subregion, an approach we call EDGE (Enhancer-Driven Gene Expression) 11 . Here we show that one can use the same approach to make rAAVs with similar specificity in both mouse and rat, provided the vector and minimal promoter's innate transcriptional activity is minimized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our prior work showed that identification of cis-regulatory elements uniquely active in finely dissected cortical subregions allows one to generate genetic tools specific to cells in that subregion, an approach we call EDGE (Enhancer-Driven Gene Expression) 11 . Here we show that one can use the same approach to make rAAVs with similar specificity in both mouse and rat, provided the vector and minimal promoter's innate transcriptional activity is minimized.…”
Section: Discussionmentioning
confidence: 99%
“…serotype, precise injections of minute quantities), we took steps to ensure that any observed specificity comes from the enhancer element used. First and foremost, we used an enhancer specific to a known subset of neurons in the entorhinal cortex 11 in transgenic animals and analyzed whether the rAAV construct could match this specificity. Figure 1A shows the expression pattern obtained from crossing one of the MEC13-53 tTA driver lines to a payload line expressing the helper transgenes for the ΔG-rabies monosynaptic tracing system 11 .…”
Section: Optimization Of Raav Design For Enhancer-driven Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are multiple inhibitory cell subtypes in the brain, and diversity within each of them (Murphey et al, 2014;Blankvoort et al, 2018). Here, we focused on subtypes defined by GAD65 (a GABA-synthesizing enzyme) and parvalbumin (a calcium-binding protein) expression because of their central roles in controlling the CP for plasticity in the mammalian primary visual cortex, the best-studied CP (Hensch et al, 1998;Takesian and Hensch, 2013;Davis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%